Risk Factors for Human Immunodeficiency Virus Infection among Brazilian Blood Donors; a Multicenter Case-Control Study Using Audio Computer-Assisted Structured-Interviews - de Almeida-Neto, Cesar (2013)
BACKGROUND: Although risk factors for HIV infection are known, it is important for blood centers to understand local epidemiology and disease transmission patterns. Current risk factors for HIV infection in blood donors in Brazil were assessed. METHODS: A case-control study was conducted at large public blood centers located in four major cities between April 2009 – March 2011. Cases were persons whose donations were confirmed positive by enzyme immunoassays followed by Western Blot confirmation. Audio computer-assisted structured-interviews (ACASI) were completed by all cases and controls. Multivariable logistic regression was used to estimate adjusted odds ratios (AORs) and associated 95% confidence intervals (CIs). RESULTS: There were 341 cases, including 47 with recently-acquired infection, and 791 controls. Disclosed risk factors for both females and males were sex with an HIV-positive person (adjusted odds ratio (AOR) 11.3, 95% CI [4.1, 31.7]) and being an IVDU or sexual partner of an IVDU (AOR 4.65 [1.8, 11.7]). For female blood donors, additional risk factors were having male sex partners who also are MSM (AOR 13.5 [3.1, 59.8]), and having unprotected sex with multiple sexual partners (AOR 5.19 [2.1, 12.9]). The primary risk factor for male blood donors was MSM activity (AOR 21.6 [8.8, 52.9.]). Behaviors associated with recently-acquired HIV were being a MSM or sex partner of MSM (13.82, [4.7, 40.3]), and IVDU (11.47, [3.0, 43.2]). CONCLUSION: Risk factors in blood donors parallel those in the general population in Brazil. Identified risk factors suggest that donor compliance with selection procedures at the participating blood centers is inadequate.